EMPLOYMENT OF VILLAGERS EFFECTIVE SOCIAL PROVISION MECHANISMS - Uzakbergenov Damir Muratbaevich; Navrizbayev Isabek Amangeldievich (Scholar Express Journals, 2023)
The article analyzes the effective social mechanisms of employment of the rural population in the service sector and provides conclusions and recommendations
Keywords: employment; macroeconomics; market infrastructure; urbanization